Novel Organotin(IV) Schiff Base Complexes with Histidine Derivatives: Synthesis, Characterization, and Biological Activity - Ariadna Garza-Ortiz; Carlos Camacho-Camacho; Teresita Sainz-Espuñes; Irma Rojas-Oviedo; Luis Raúl Gutiérrez-Lucas; Atilano Gutierrez Carrillo; Marco A. Vera Ramirez (Bioinorganic Chemistry and Applications)
Five novel tin Schiff base complexes with histidine analogues (derived from the condensation reaction between L-histidine and 3,5-di-tert-butyl-2-hydroxybenzaldehyde) have been synthesized and characterized. Characterization has been completed by IR and high-resolution mass spectroscopy, 1D and 2D solution NMR (1H, 13C  and 119Sn), as well as solid state 119Sn NMR. The spectroscopic evidence shows two types of structures: a trigonal bipyramidal stereochemistry with the tin atom coordinated to five donating atoms (two oxygen atoms, one nitrogen atom, and two carbon atoms belonging to the alkyl moieties), where one molecule of ligand is coordinated in a three dentate fashion. The second structure is spectroscopically described as a tetrahedral tin complex with four donating atoms (one oxygen atom coordinated to the metal and three carbon atoms belonging to the alkyl or aryl substituents), with one molecule of ligand attached. The antimicrobial activity of the tin compounds has been tested against the growth of bacteria in vitro to assess their bactericidal properties. While pentacoordinated compounds 1, 2, and 3 are described as moderate effective to noneffective drugs against both Gram-positive and Gram-negative bacteria, tetracoordinated tin(IV) compounds 4 and 5 are considered as moderate effective and most effective compounds, respectively, against the methicillin-resistant Staphylococcus aureus strains (Gram-positive).